Wnt10b signaling regulates replication stress-induced chromosomal instability in human cancer - Haas, Alexander; Wenz, Friederike; Hattemer, Janina; Wesslowski, Janine; Davidson, Gary; Voloshanenko, Oksana; Boutros, Michael; Acebron, Sergio P.; Bastians, Holger (Life science alliance, 2025)
Wnt signaling pathways are involved in various developmental and tissue maintenance functions, whereas deregulated Wnt signaling is closely linked to human cancer. Recent work revealed that loss of Wnt signaling impairs mitosis and causes abnormal microtubule growth at the mitotic spindle resulting in chromosome missegregation and aneuploidy, both of which are hallmarks of cancer cells exhibiting chromosomal instability (CIN). Here, we show that upon DNA replication stress, a condition typically associated with CIN, Wnt10b acts to prevent increased microtubule dynamics from the S phase until mitosis, thereby ensuring faithful chromosome segregation. Interestingly, replication stress-induced chromosomal breaks are also efficiently suppressed by Wnt10b. Thus, our results show that Wnt10b signaling regulates replication stress-induced chromosome missegregation and breakage, and hence is a determinant for broad genome instability in cancer cells.